Database management systems - Ramakrishnan, Raghu (McGraw-Hill, 2000)
"Database Management Systems (DBMS) is a must for any course in database systems or file organization. DBMS provides a hands-on approach to relational database systems, with an emphasis on practical topics such as indexing methods, SQL, and database design. New to this edition are the early coverage of the ER model, new chapters on Internet databases, data mining, and spatial databases, and a new supplement on practical SQL assignments (with solutions for instructors' use). Many other chapters have been reorganized or expanded to provide up-to-date coverage."